Technical essential aspects in robotic colorectal surgery: mastering the Da Vinci Si and Xi platforms - MORRELL,ANDRE LUIZ GIOIA (2021)
ABSTRACT Background: laparoscopy surgery has many proven clinical advantages over conventional surgery and more recently, robotic surgery has been the emerging platform in the minimally invasive era. In the colorectal field, although overcoming limitations of standard laparoscopy, robotic surgery still faces challenging situations even by the most experienced colorectal surgeons. This study reports essentials technical aspects and comparison between Da Vincis Si and Xi platforms aiming to master and maximize efficiency whenever performing robotic colorectal surgery. Methods: this study overviews the most structured concepts and practical applications in robotic colorectal surgery in both Si and Xi Da Vinci platforms. Possible pitfalls are emphasized and step-wise approach is described from port placement and docking process to surgical technique. We also present data collected from a prospectively maintained database. Results: our early experience includes forty-four patients following a standardized total robotic left-colon and rectal resection. Guided information and practical applications for a safe and efficient robotic colorectal surgery are described. We also present illustrations and describe technical aspects of a standardized procedure. Conclusion: performing robotic colorectal surgery is feasible and safe in experienced surgeons hands. Although the Da Vinci Xi platform demonstrates greater versatility in a more user-friendly design with technological advances, the correct mastery of technology by the surgical team is an essential condition for its fully robotic execution in a single docking approach.